Final answer:
To evaluate the expression -3^2(2-6(10)), follow the order of operations: calculate parentheses, evaluate exponent, substitute values, and perform multiplication.
Step-by-step explanation:
To evaluate the given expression -3^2(2-6(10)), we need to follow the order of operations (PEMDAS/BODMAS). Let's break it down step by step:
- First, we evaluate the parentheses (2-6(10)) = 2-60 = -58.
- Next, we calculate the exponent (-3^2) = (-3)(-3) = 9.
- Now, we can substitute the values back into the expression: -58 × 9 = -522.
Therefore, the value of the given expression is -522.